A novel palaeoaltimetry proxy based on spore and pollen wall chemistry - Lomax,BH; Fraser,WT; Harrington,G; Blackmore,S; Sephton,MA; Harris,NBW (Earth and Planetary Science Letters, 2012)
Understanding the uplift history and the evolution of high altitude plateaux is of major interest to a wide range of geoscientists and has implications for many disparate fields. Currently the majority of palaeoaltimetry proxies are based on detecting a physical change in climate in response to uplift, making the relationship between uplift and climate difficult to decipher. Furthermore, current palaeoaltimetry proxies have a low degree of precision with errors typically greater than 1 km. This makes the calculation of uplift histories and the identification of the mechanisms responsible for uplift difficult to determine. Here we report on advances in both instrumentation and our understanding of the biogeochemical structure of sporopollenin that are leading to the establishment of a new proxy to track changes in the flux of UV-B radiation over geological time. The UV-B proxy is based on quantifying changes in the concentration of UV-B absorbing compounds (UACs) found in the spores and pollen grains of land plants, with the relative abundances of UACs increasing on exposure to elevated UV-B radiation. Given the physical relationship between altitude and UV-B radiation, we suggest that the analysis of sporopollenin chemistry, specifically changes in the concentration of UACs, may offer the basis for the first climate independent palaeoaltimetry proxy. Owing to the ubiquity of spores and pollen in the fossil record, our proposed proxy has the potential to enable the reconstruction of the uplift history of high altitude plateaux at unprecedented levels of fidelity, both spatially and temporally.